Screening of Endophytic Bacteria Isolated from Marine Sponge Haliclona fascigera for Inhibition against Clinical Isolates of Methicillin Resistant Staphylococcus aureus (MRSA) - Dian Handayani, Neny Sandrawaty, Murniati Murniati, Regina Regina (Journal of Applied Pharmaceutical Science, 2015)
Marine endophytic bacteria are a valuable source of novel antibacterial in combating pathogenic isolates of methicillin-resistant Staphylococcus aureus (MRSA), a global nosocomial problem today. The aim of this study was to assess in vitro anti-MRSA activity of extracts from bacteria endophyte of marine sponge Haliclona fascigera collected from Setan Island, South Coast of West Sumatra, Indonesia. Anti-MRSA activity test carried out by the agar diffusion method using paper disk. The endophytic bacteria from sponge were isolated using dilution method and pour plate method on NA media. From the sponge were obtained 26 isolates of bacterial endophytic then propagated in NB media. The liquid media was then extracted using ethyl acetate solvent. Antimicrobial activity test carried out by the agar diffusion method using paper disk. The antibacterial activity assay was conducted with the extract concentrations of 5 %. Chloramphenicol was used as a positive control agent. The zone of inhibition was measured and expressed in millimeters. There were 12 isolates of the bacteria that considered active to MRSA. Mean of inhibition zones ranged from 11.1±0.17 to 15.17±0.76. Characterization and identification of endophytic bacteria were conducted to several bioactive bacteria. The identification method was performed using Gram staining and biochemical test.
Keywords: Anti-MRSA activity, Marine sponge, Haliclona fascigera, Endophytic bacteria.